The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.23922/jarc.2020-081
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Late Rebleeding of Colonic Diverticular Bleeding in Elderly Individuals

Abstract: Objectives: This study aimed to examine the clinical characteristics of colonic diverticular bleeding (CDB) in elderly individuals. Methods: This retrospective case-control study was conducted at a single tertiary center. A total of 519 patients (356 men and 163 women; mean age of 73.1 ± 12.5 years) with CDB and hospitalized between January 2004 and May 2019 were analyzed. The subjects were divided into two groups: the elderly (274 individuals aged ! 75 years; mean age, 82.1 ± 5.3 years) and non-elderly (245 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Interestingly, our study identified that the location of the colon diverticula was associated with the occurrence of rCDB. Patients with bilateral colon diverticula had a higher occurrence of rCDB, which was similar to previous studies (24,26,27). We also demonstrated that patients with sigmoid colon diverticula had a higher occurrence of rCDB.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our study identified that the location of the colon diverticula was associated with the occurrence of rCDB. Patients with bilateral colon diverticula had a higher occurrence of rCDB, which was similar to previous studies (24,26,27). We also demonstrated that patients with sigmoid colon diverticula had a higher occurrence of rCDB.…”
Section: Discussionsupporting
confidence: 91%